Understanding moral obligation : Kant, Hegel, Kierkegaard - Stern, Robert, 1962- (Cambridge ; Cambridge University Press, 2012)
'In many histories of modern ethics, Kant is supposed to have ushered in an anti-realist or constructivist turn by holding that unless we ourselves'author' or lay down moral norms and values for ourselves, our autonomy as agents will be threatened. In this book, Robert Stern challenges the cogency of this'argument from autonomy', and claims that Kant never subscribed to it. Rather, it is not value realism but the apparent obligatoriness of morality that really poses a challenge to our autonomy: how can this be accounted for without taking away our freedom? The debate the book focuses on therefore concerns whether this obligatoriness should be located in ourselves (Kant), in others (Hegel) or in God (Kierkegaard). Stern traces the historical dialectic that drove the development of these respective theories, and clearly and sympathetically considers their merits and disadvantages; he concludes by arguing that the choice between them remains open'--
Machine generated contents note: Acknowledgements; References and abbreviations; Introduction; Part I. Kant: 1. Kant, moral realism, and the argument from autonomy; 2. The argument from autonomy and the problem of moral obligation; 3. Kant's solution to the problem of moral obligation; Part II. Hegel: 4. Hegel's critique of Kant (via Schiller); 5. Hegel's solution to the problem of moral obligation; Part III. Kierkegaard: 6. Kierkegaard's critique of Hegel; 7. Kierkegaard's solution to the problem of moral obligation; Conclusion: from Kant to Kierkegaard - and back again?; Bibliography.
Includes bibliographical references (p. 255-272) and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Kierkegaard, S{u296E}, -- 1813-1855.; Duty; Responsibility; PHILOSOPHY / History & Surveys / General